PEMBELAJARAN BERDIFERENSIASI DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH: A NARRATIVE LITERATURE REVIEW - Herdianto Wahyu Pratomo; Jihan Ramadhan; Fahmie Firmansyah; Wisudatul Ummi; Andi Nurul Tenriwali Hasanuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The Merdeka Curriculum in Indonesia presents challenges and opportunities in adapting education to individual needs through differentiated learning. This literature review examines the implementation of differentiated learning in schools within the framework of the Merdeka Curriculum, focusing on the forms of implementation of differentiated learning in schools. The literature review was conducted on various articles published from 2020 to 2023, using a literature search, selection, analysis, and synthesis process, thus mapping the forms of differentiated learning implementation within the Merdeka curriculum. The research results show that implementing differentiated learning within the framework of the Merdeka curriculum in schools includes various forms, namely content adjustment, adjustment of learning processes, assessment methods, and adjustment of learning products. These forms of implementation represent adjustments to the framework of the Merdeka curriculum